Manipulation on trial : economic analysis and the Hunt silver case / Jeffrey Williams. - Williams, Jeffrey, 1953- (Cambridge University Press, 1995)
The unprecedented rise and fall in silver's price during 1979 and 1980 resulted in charges against the Hunt brothers of Dallas of monopolization and market manipulation, charges which led to a lengthy trial. This book focuses on the economic analysis used at this trial. Drawing upon interviews with the judge, jury, attorneys and expert witnesses (the author having so served), it investigates the elusive definition of manipulation in sophisticated markets, the difficulties of interpreting statistical evidence, the imprecision in calculating damages, the hidden assumptions behind inferences concerning intent, and the hazards introduced when economic analysis enters complex litigation. The author concludes that these problems induce courtroom procedures to oversimplify the economic analysis and cause the law on market manipulation to be created retroactively. Yet the failure lies not with the legal institutions but with the futures exchanges who had not developed in advance the rules to minimize large-scale trading during the unusual price moves.